Phenomenon of archaics in organization of sociocultural process - Lamazhaa, Chimiza K. (The New Research of Tuva, 2014)
Review of round table "Phenomenon of archaics in organization of sociocultural process” held on June 22, 2014 in the Republic of Tuva within the framework of XII International Seminar "Ethnosocial processes in Siberia: sociocultural approach to regional ethnonational policies”.
Keywords: round table; review; archaic; archaization